2015
DOI: 10.1186/s40337-015-0082-y
|View full text |Cite
|
Sign up to set email alerts
|

Schema modes in eating disorders compared to a community sample

Abstract: BackgroundThe aim of this study was to examine the association between eating disorders (ED) and schema modes, and identify which specific schema modes are associated with particular eating disorders, including anorexia nervosa (AN), bulimia nervosa (BN) and other specified feeding or eating disorder (OSFED).MethodsA total of forty seven women with eating disorders and 89 women from the community participated in this study. Eating disorder diagnosis was determined by a clinician treating the eating disorder an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 23 publications
9
24
0
2
Order By: Relevance
“…[6, 30]). Although the Self-Aggrandiser mode also functions as a form of overcompensation, this mode was endorsed at a relatively low level and only weakly correlated with eating behaviours, consistent with previous findings [45, 49]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[6, 30]). Although the Self-Aggrandiser mode also functions as a form of overcompensation, this mode was endorsed at a relatively low level and only weakly correlated with eating behaviours, consistent with previous findings [45, 49]. …”
Section: Discussionsupporting
confidence: 91%
“…These findings support previous theory suggesting the need to consider developmental factors and the function of ED behaviours in conjunction with maintenance factors, when conceptualising and treating EDs [36, 39, 45, 54]. The study also emphasises that treatment of EDs cannot rely solely on trait-based factors (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Prior research in the field found higher overall levels of EMS both in those with eating disorder symptomatology and substance abuse, including binge drinking, compared to controls (Boone, Braet, Vandereycken, & Claes, 2013;Brotchie et al, 2004;Damiano, Reece, Reid, Atkins, & Patton, 2015;Dingemans, Spinhoven, & van Furth, 2006;Elmquist, Shorey, Anderson, & Stuart, 2015;Jones, Harris, & Leung, 2005;Jones et al, 2007;Leung, Waller, & Tomas, 1999;Pauwels et al, 2013;Shorey et al, 2014;Shorey et al, 2013a;Talbot, Smith, Tomkins, Brockman, & Simpson, 2015;Unoka, Tölgyes, Czobor, & Simon, 2010;Waller et al, 2000). Furthermore, higher endorsement of EMS has been associated with poorer treatment outcomes in these populations (e.g., Jones et al, 2007;Leung, Waller, & Thomas, 2000).…”
Section: Ems and Eating And Drinking Pathologymentioning
confidence: 98%